2015
DOI: 10.1007/s00107-015-0891-3
|View full text |Cite
|
Sign up to set email alerts
|

Study of stress distribution and stress concentration factor in notched wood pieces with cohesive surfaces

Abstract: In this study, the stress distribution and stress concentration factor (SCF) of a generic notched wood piece and ASTM D 143:14 notched shear block specimen were analysed. A 2D plane stress finite element model with linear elastic behaviour was assumed for the bulk material and a predefined potential crack path and cohesive behaviour of the crack surfaces were considered. Wood was considered an orthotropic material with transversal isotropy. In the notched wood pieces, the shear stress distribution along the sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…These results confirm the distribution presented in Figure 14, a triangular diagram with a slope increase to the contact face, which represents an SCF greater than two. This distribution is in accordance with other studies (3,5,49,50), a half hammock shape as reported by Verbist et al (11), but even more intense when reaching the corner side in the shear path. These results for the SCF indicates that the theoretical uniform shear stress is around 0.36 (SCF FEM = 2.77 -2.79) and 0.47 (SCF EXP = 2.13) of the highest shear stress reached.…”
Section: Stress Behaviour Of the Jointsupporting
confidence: 93%
“…These results confirm the distribution presented in Figure 14, a triangular diagram with a slope increase to the contact face, which represents an SCF greater than two. This distribution is in accordance with other studies (3,5,49,50), a half hammock shape as reported by Verbist et al (11), but even more intense when reaching the corner side in the shear path. These results for the SCF indicates that the theoretical uniform shear stress is around 0.36 (SCF FEM = 2.77 -2.79) and 0.47 (SCF EXP = 2.13) of the highest shear stress reached.…”
Section: Stress Behaviour Of the Jointsupporting
confidence: 93%
“…As illustrated in Figure 8, the design rafter load-bearing capacity, noted , , , must be checked by the equations (1)-(17)-(18)- (19), similar to (9)-(10)-(11) from the SSJ design, in order to prevent the appearance of shear crack in the tie beam for each DSJ heel [6][7][8]25].…”
Section: Dsj Design Model Against the Shear Crackmentioning
confidence: 99%
“…[13,14,15,16]), recent research (e.g. [17,18,19,20,21,22,24,25]) and state-of-the arts (e.g. [6,7,12,23,26]) have focused on determining the mechanical behaviour of the three SJ typologies through analytical, numerical and experimental assessments.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations